Comprehensive validation of a custom three-point bending system for standardized diabetic fracture models in rats - Qidong Guo; Weijie Wang; Zheng Guo (Journal of Orthopaedic Surgery and Research)
Abstract Background Diabetes mellitus (DM) significantly impairs fracture healing, necessitating reliable animal models to study diabetic fracture repair mechanisms and therapeutic interventions. This study aimed to develop and comprehensively validate a standardized three-point bending system for inducing precise, reproducible mid-shaft transverse femoral fractures in rats, addressing existing methodological gaps of insufficient reproducibility and detailed calibration in previous models. Methods A custom-designed three-point bending fracture induction system was developed using AutoCAD software based on the original principle introduced by Einhorn et al. (1984). After manufacturing and calibration, the system was validated first using 22 cadaveric rat femurs and subsequently applied to live rats (n = 44), including diabetic (streptozotocin-induced, n = 22) and non-diabetic animals (n = 22). Fracture induction reproducibility was assessed through radiographic, histologic and mechanic analysis. Additionally, statistical analysis was conducted using GraphPad Prism 9 software. Coefficients of variation (CV) for fracture-healing parameters (callus diameter, calcification ratio, maximum bending force at re-fracture) were calculated and compared statistically with similar parameters from previously published rat femoral fracture studies. Results Cadaveric validation confirmed that the optimal blade travel distance, set as half the femoral diameter, consistently produced standardized transverse fractures without comminution. A significant correlation between body weight and femoral diameter (Femoral diameter = 1.0276 ln [Body weight] − 1.349) allowed accurate preoperative determination of optimal blade travel distance. Live animal testing demonstrated consistent fracture patterns, stable intramedullary pin fixation, and no complications during surgical procedures. Statistical analysis revealed significantly lower coefficients of variation for healing parameters in this study compared to previously published models (p < 0.05). Histological analysis indicated the fracture type was transverse. Callus was found around fracture site. Conclusion Our validated three-point bending system significantly enhances reproducibility, consistency, and methodological rigor in animal fracture research. This standardized model provides an ideal foundation for future preclinical studies investigating diabetic fracture healing mechanisms and potential therapeutic interventions.